Employee Performance Improvement Based on the Big Five Personality with Self-Efficacy as a Mediation Aspect - Suhermin; Fatmawati, Endang (Optima Science, 2023)
The purpose of this study is to determine the increase in employee performance based on the Big Five Personality with Self-Efficacy as a mediating aspect. This research is included in the type of explanatory research. This research was conducted on Gemilang Putra & Co employees located in Jember, East Java. The object of this research is the Big Five Personality, Self-Efficacy, and Employee Performance. Sources of data in this study were obtained through the company's internal data. The types of data used are primary data and secondary data. The population in this study were 30 employees and the sampling technique used was saturated sampling, so that all members of the population could be used as research samples because the respondents were less than 30 employees. The tests used in this research are validity test, reliability test, descriptive statistical analysis, path analysis, path assumption test, and hypothesis testing. The results of the study show that the Big Five Personality has a significant effect on Self-Efficacy, the Big Five personality has a significant effect on employee performance, Self-Efficacy has a significant effect on employee performance, and the Big Five Personality mediated by Self-Efficacy has a significant effect on employee performance.